A New Construction of Fermi-Walker Derivative by Focal Curves According to Modified Frame - Yeneroglu, Mustafa; Korpinar, Talat (Amer Scientific Publishers, 2018)
In this paper, we obtain a characterization of focal curves by Fermi-Walker parallelism and derivative with modified frame. Furthermore, we have a new results Fermi-Walker parallelism and derivative for a focal curve according to modified frame in space. Finally, we obtain some new solutions of differential equations by Fermi-Walker parallel field.
Keywords: Modified Frame; Fermi Walker Derivative-Parallelism; Focal Curve